Summer rental - Andrews, Mary Kay, 1954- (New York : St. Martin's Press, 2011)
Ellis questions everything she believed after losing an all-consuming job, while Julia struggles with insecurities that threaten a loving relationship and Dorie confronts a maelstrom of problems after a shocking betrayal.
English Language & Literature.
Keywords: Women -- Fiction; Female friendship -- Fiction; Summer -- Fiction; Vacations -- Fiction; Outer Banks (N.C.) -- Fiction; Love stories